Manipulating cognitive engagement in preparation-to-collaborate tasks and the effects on learning. (December 2017) - Lam, Rachel; Muldner, Kasia
Abstract: While collaborating with a peer can be highly beneficial for learning, more work is needed to understand how instructional activities in collaborative contexts should be designed so as to maximize learning outcomes. To address this, we investigated the impact of different types of preparatory and cognitively engaging tasks on learning from collaborating, using a 2 × 2 experimental study conducted in situ in four introductory psychology classes. We compared individual preparation versus no-preparation and "active" versus "constructive" tasks. A dyadic multilevel analysis showed that preparation prior to collaborating led to better deep learning outcomes, but that the type of preparation did not have a significant effect. We include an exploratory analysis of student dialogues during collaboration to further interpret our findings. We propose that a cognitively engaging preparation phase may lead to better learning because it encourages students to collaborate constructively even when the type of task does not elicit such engagement. Highlights: ICAP and PFL theoretical models can be used to design collaborative learning tasks. Preparation-to-collaborate leads to better transfer outcomes than no preparation. Compared to a collaborative Active task, a Constructive task seems to invoke more constructive interaction. Active & Constructive preparation similarly affect collaborative learning outcomes. Active preparation can invoke constructive engagement in collaboration.